The Symbiotic Sisterhood: Analyzing Rituals of Shared Grief in “Midsommar” - Ramadhania, Mutiara (Journal Corner of Education, Linguistics, and Literature, 2025)
This research explored the portrayal of shared grief and communal healing in Ari Aster’s film “Midsommar”, focusing on the “Harga” community’s rituals through the lenses of Emile Durkheim’s functionalism and Ferdinand de Saussure’s visual-semiotic theory. The research investigates how these rituals foster a “symbiotic sisterhood” and facilitate the protagonist Dani’s transformation from isolation to belonging. Using qualitative visual-semiotic analysis, the study decodes the film’s symbolic imagery, communal ceremonies, and structured cultural practices. The findings reveal that the Harga's ritualistic expressions of grief—such as the Attestupa and communal crying—serve not only as mechanisms for emotional release but also reinforce social cohesion, mirroring Durkheim’s theory of collective effervescence and organic solidarity. Dani’s participation in these rites catalyzes her psychological recovery from trauma, positioning the Harga women as a therapeutic support system. The study concludes that “Midsommar” subverts traditional Western notions of solitary mourning by presenting grief as a collective, functional force that forges identity, solidarity, and empowerment within a closed communal structure. This analysis contributes to broader discussions on how horror films visualize trauma, ritual, and gendered communal bonds in popular culture.